Conditioned medium of amniotic fluid‐derived stromal cells exerts a bone anabolic effect by enhancing progenitor population and angiogenesis. (12th July 2022) - Song, Min‐Kyoung; Sun, Hyun Jin; Cho, Sun Wook
Abstract: A cell‐free approach utilizing the paracrine effects of mesenchymal stromal cells is receiving attention in regenerative medicine. In the present study, we evaluated the effects of a conditioned medium of amniotic fluid‐derived stromal cells (AFSC‐CM) on bone metabolism. In mice, intraperitoneal injections of AFSC‐CM increased bone mass and enhanced bone turnover. The precursor populations of myeloid and mesenchymal lineages, as well as endothelial cells in bone marrow, were also augmented by AFSC‐CM administration. In an in vitro culture experiment, AFSC‐CM increased osteoclast differentiation of bone marrow‐derived macrophages, but had no significant effect on the osteogenic differentiation of preosteoblasts. However, AFSC‐CM administration dramatically accelerated the migration and tube formation of endothelial cells, and a cytokine array showed that AFSC‐CM contained many angiogenic factors. These results indicate that AFSC‐CM exerts a bone anabolic effect by changing the bone marrow microenvironment, including angiogenesis and precursor expansion. Therefore, ameliorating marrow angiogenesis is a potential therapeutic strategy for bone regeneration, for which AFSCs can be a good cellular source.